(untitled) (FUDMA JOURNAL OF SCIENCES, 2025)
This study investigates heat and mass transfer flow through a porous medium with variable thermal conductivity and suction effects. Unsteady natural convection with magnetic field, radiation and pressure gradient were considered. Perturbation method was employed to derive analytical expressions for the dimensionless velocity, temperature, and concentration profiles. The influence of key dimensionless parameters—including variable thermal conductivity, temperature and mass buoyancy parameters (), magnetic field strength, suction parameter, Darcy number (), mass Grashof numbers (), radiation parameter (), Prandtl number (), chemical reaction rate (), Schmidt number (), and pressure gradient —were analyzed in detail. Results showed: increased in , (), (), (), and () enhanced velocity while , () and suppressed it. Temperature rises with increased , () and () but decreased with and (). Species concentration decreased with stronger (), () and (). Additionally, Skin friction (), Nusselt number () and Sherwood number () exhibited significant sensitivity to variations in the governing parameters. The findings provided valuable insight into flow behavior in porous media with applications in geophysics, chemical engineering, and energy systems.